The management of Accident in the Oil and Gas Servicing Firms in Nigeria through Workplace Safety Programs (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Organization in the course of the discharge of their activities in the workplace encounter both inherent and potential hazards. The manifestation or occurrence of this accident in the discharge of assigned exude grievous negative impact to not just the injured but the organization at large. It affects the output level, integrity of the firm and its image, growth and survival and continues operation. It has a telling effects on the firms in terms of lost work days, medical bills, compensation, fines, delay production as a result of facility/plant shut down etc. given this cost implications, organization are in constant need of models and programs to stern this tide. Given the integral nature of this all-time desire and in the realization of this, lot of scholarly works have been advanced postulating and prescribing models and theories on how to achieve this feat. Some of those have yielded results while others have not. In the light of this desire we attempt to examine the workplace safety models and program which is considered to be elaborate, robust and all-encompassing and thus, situate it within the Nigeria oil and gas work sector and investigate how this can impact on accident management. To put the study in perspective, workplace safety program was measured using management commitment, worksite inspection, training and education and safety culture and accident was measured by the occurrence of injury. Four null hypotheses deduced from literature was structured to put the work in working context. After a critical analysis adopted using structural equation modelling through the AMOS package several findings were made upon which some recommendations were equally advanced.